Charm fragmentation fractions and cc[bar] cross section in p-Pb collisions at √sNN = 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Nath, Abhishek; et al. (The European physical journal. C, Particles and fields, 2024)
The total charm-quark production cross section per unit of rapidity $$\textrm{d}\sigma ({{\textrm{c}}\overline{\textrm{c}}})/\textrm{d}y$$, and the fragmentation fractions of charm quarks to different charm-hadron species $$f(\textrm{c}\rightarrow {\textrm{h}}_{\textrm{c}})$$, are measured for the first time in p-Pb collisions at $$\sqrt{s_\textrm{NN}} = 5.02~\text {Te}\hspace{-1.00006pt}\textrm{V} $$at midrapidity ($$-0.96<y<0.04$$in the centre-of-mass frame) using data collected by ALICE at the CERN LHC. The results are obtained based on all the available measurements of prompt production of ground-state charm-hadron species: $$\textrm{D}^{0}$$, $$\textrm{D}^{+}$$, $$\textrm{D}_\textrm{s}^{+}$$, and $$\mathrm {J/\psi }$$mesons, and $$\Lambda _\textrm{c}^{+}$$and $$\Xi _\textrm{c}^{0}$$baryons. The resulting cross section is $$ \textrm{d}\sigma ({{\textrm{c}}\overline{\textrm{c}}})/\textrm{d}y =219.6 \pm 6.3\;(\mathrm {stat.}) {\;}_{-11.8}^{+10.5}\;(\mathrm {syst.}) {\;}_{-2.9}^{+8.3}\;(\mathrm {extr.})\pm 5.4\;(\textrm{BR})\pm 4.6\;(\mathrm {lumi.}) \pm 19.5\;(\text {rapidity shape})+15.0\;(\Omega _\textrm{c}^{0})\;\textrm{mb} $$, which is consistent with a binary scaling of pQCD calculations from pp collisions. The measured fragmentation fractions are compatible with those measured in pp collisions at $$\sqrt{s} = 5.02$$and 13 TeV, showing an increase in the relative production rates of charm baryons with respect to charm mesons in pp and p-Pb collisions compared with $$\mathrm {e^{+}e^{-}}$$and $$\mathrm {e^{-}p}$$collisions. The $$p_\textrm{T}$$-integrated nuclear modification factor of charm quarks, $$R_\textrm{pPb}({\textrm{c}}\overline{\textrm{c}})= 0.91 \pm 0.04\;\mathrm{(stat.)} ^{+0.08}_{-0.09}\;\mathrm{(syst.)} ^{+0.05}_{-0.03}\;\mathrm{(extr.)} \pm 0.03\;\mathrm{(lumi.)}$$, is found to be consistent with unity and with theoretical predictions including nuclear modifications of the parton distribution functions.
*ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, J. Crkovska, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grunwald, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone [sehr viele weitere Personen]
Gesehen am 06.08.2025
Im Titel steht der 2. Buchstabe c mit einem Oberstrich
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol